THE SOCIOPOLITICAL ENTANGLEMENT OF SUFISM - M Thohar Al Abza; Kamsi Kamsi Kamsi; Nawari Ismail (IAIN Tulungagung, 2019)
Sufi group (tarekat) mainly dictates its followers to distance themselves from worldy affairs and to live in religious seclusion (zuhud). This article offers a distinct perspective on the study of sufism through examining the political activities of the sufi group the Tarekat Qadiriyah wa Naqsyabandiyah of Cukir in Indonesia and the group’s political patron, the Partai Persatuan Pembangunan (PPP). The article benefits form a French philosopher Michel Foucault’s concept of geneology and the notion of knowledge to better comprehend the nature of political activism of a sufi group. It further argues that basic concept of student and master (murshid) relationship in Sufism is explaining the politics of sufism in contemporary Indonesia. The mutual relation between leaders of the sufi group and the PPP has facilitated the crossing boundaries of sufi basic principle of non-participatory politics.